Pain intensity measurements in patients with acute pain receiving afferent stimulation. - Ekblom, A (1988)
Six different pain rating scales, including a "pain relief scale", were compared in 80 patients suffering acute orofacial pain. Pain intensity measurements were made before and after a 30 min period of afferent stimulation (TENS/vibration and placebo). A good correlation was found between pain scores derived from the pain relief scale, visual analogue-, numerical- and graphic rating scales. The verbal rating scale did not perform well. The pain relief scale and the numerical rating scale are interesting alternatives to the established visual analogue scale.